ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN VIRTUAL REALTY TOUR PADA KEMAMPUAN LITERASI MATEMATIKA - Nur Hasanah; Intan Pramuditya Hartanti; Wahyu Nur Amin; Ayu Putri Regita Sari; Eko Andy Purnomo (Universitas Muhammadiyah Semarang, 2023)
Mathematical literacy ability is a person's ability to apply mathematical concepts in everyday life. However, the importance of this ability is not balanced by the low mathematics literacy scores of Indonesian students. The aim of this research is to collect data regarding learning media using virtual reality tour website technology to help improve mathematical literacy skills. The method used in this research is R&D with the ADDIE model. The sampling technique in this research was a cross-sectional study. Meanwhile, data collection techniques were carried out by means of observation, interviews and distributing questionnaires in the form of questionnaires. This research focuses on analyzing learning media needs for teachers and students at MTs Islamiyyah Syafi'iyah Gandrirojo and SMP IT Avicenna in Rembang district. The research results show that teachers need learning media that is interesting, interactive, easy to explore and able to visualize everyday life to improve students' mathematical literacy skills. This is also supported by the results of the student needs analysis questionnaire which stated that students were interested and agreed that a virtual reality tour website media would be developed to help apply mathematical concepts into everyday life.